Research on Modeling and Compensation of Generalized Kinematic Error of RCM Manipulators for Minimally Invasive Surgery Robots - Liu Fen; Wang Rui; Huang Fang; Sang Hongqiang (Jixie chuandong)
There is a safety issue for geometric and non-geometric errors that lead to remote center of motion (RCM) constraint point position errors during the movement of the RCM manipulator. A generalized kinematic error modeling and compensation method is proposed for the RCM manipulator of minimally invasive surgical robots. Firstly, an error model characterizing the joint-dependent kinematic errors caused by geometric and non-geometric errors is established based on the Chebyshev polynomial. Then, the polynomial coefficients and kinematic parameter errors in the error model are identified by the least squares method. Finally, the joint space compensation method is employed to reduce the RCM constraint point position errors. The experiment results show that the RCM constraint point position errors after compensation are reduced from 2.726 1 mm to 0.641 5 mm, which is 76.5% less.